2020
DOI: 10.1055/s-0040-1707158
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzo-Fused 11H-Pyrido[2,1-b]quinazolin-11-ones by a Buchwald–Hartwig Coupling/Pyridine Dearomatization Sequence in Eucalyptol

Abstract: The synthesis of a new library of polyheterocyclic 11H-pyrido[2,1-b]quinazolin-11-one derivatives was investigated. Satisfactory conditions were obtained via sequential C–N Buchwald–Hartwig coupling and pyridine dearomatization. In this work, traditional solvents were replaced by the bio-sourced eucalyptol, confirming the interest in it as a green solvent in chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…1 H NMR (300 MHz, DMSO-d 6 ):  = 9.50 (s, 1 H), 8.44 (d, J = 8.8 Hz, 1 H), 7.71 (d, J = 8.7 Hz, 1 H), 4.05 (t, J = 6.1 Hz, 2 H), 2.99 (t, J = 6.6 Hz, 2 H), 2.02-1.79 (m, 4 H). 13 C NMR (75 MHz, DMSO-d 6 ):  = 160. 13, 158.30, 155.80, 151.18, 146.08, 129.76, 128.88, 125.15, 114.15, 42.35, 31.35, 21.31, 18. 1 H NMR (300 MHz, DMSO-d 6 ):  = 8.56 (d, J = 8.9 Hz, 1 H), 7.86 (d, J = 8.9 Hz, 1 H), 4.07 (t, J = 6.1 Hz, 2 H), 3.04 (t, J = 6.5 Hz, 2 H), 2.02-1.87 (m, 4 H).…”
Section: 8910-tetrahydro-12h-pyrido[21-b]thiazolo[54-f]quinazolin-12-...mentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR (300 MHz, DMSO-d 6 ):  = 9.50 (s, 1 H), 8.44 (d, J = 8.8 Hz, 1 H), 7.71 (d, J = 8.7 Hz, 1 H), 4.05 (t, J = 6.1 Hz, 2 H), 2.99 (t, J = 6.6 Hz, 2 H), 2.02-1.79 (m, 4 H). 13 C NMR (75 MHz, DMSO-d 6 ):  = 160. 13, 158.30, 155.80, 151.18, 146.08, 129.76, 128.88, 125.15, 114.15, 42.35, 31.35, 21.31, 18. 1 H NMR (300 MHz, DMSO-d 6 ):  = 8.56 (d, J = 8.9 Hz, 1 H), 7.86 (d, J = 8.9 Hz, 1 H), 4.07 (t, J = 6.1 Hz, 2 H), 3.04 (t, J = 6.5 Hz, 2 H), 2.02-1.87 (m, 4 H).…”
Section: 8910-tetrahydro-12h-pyrido[21-b]thiazolo[54-f]quinazolin-12-...mentioning
confidence: 99%
“…In a microwave vial, a solution of mackinazolinone derivative 1a (0.050 g, 0.2 mmol), 4-hydroxybenzaldehyde (0.095 g, 0.8 mmol, 4.0 equiv), and NaOAc (0.064 g, 0.8 mmol, 4.0 equiv) in glacial AcOH (0.1 M, 0.2 mL) was heated at 140 °C (microwave irradiation) for 2 h. The resulting mixture was concentrated under reduced pressure and the (d, J = 8.8 Hz, 1 H), 4.21-4.13 (t, J = 7.9 Hz, 2 H), 3.17 (t, J = 7.9 Hz, 2 H), 2.24 (quint, J = 7.9 Hz, 2 H). 13 C NMR (75 MHz, DMSO-d 6 ):  = 160. 74, 158.94, 158.44, 151.32, 147.94, 129.72, 128.66, 125.46, 114.38, 46.70, 32 30, 159.96, 158.52, 151.46, 145.97, 130.15, 128.85, 125.44, 114.11, 42.55, 36.73, 28.83, 27.21…”
Section: H-pyrido[21-b]thiazolomentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,[25][26][27] Eucalyptol has been investigated as a greener or more sustainable nonperoxide forming ether solvent for several coupling reactions, but such a system still suffers from a number of drawbacks, including moderate yields and high boiling point, thus making product isolation energy intensive. 2,[28][29][30] However, the application of TMO and DEDMO in coupling reactions is limited and further investigation is needed to highlight the full potential of these safer ether solvents. 31 TMO has recently been used as a solvent in Pd-catalyzed Hartwig-Buchwald coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the above, it seemed important to explore this synthesis approach in order to improve general knowledge in the eld of new and greener synthetic strategies for the construction of O,S,N-heterocycles. [12][13][14][15][16][17][18][19][20][21] To prepare the benzothiazole skeleton, and aer reviewing the literature, we found that Ramakrishnan's team had successfully used the potential of photochemical synthesis. The photocyclization of halogenated thioacetanilides gave a high yield of halogenated 2methylbenzothiazoles (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%